Pesan Profetik Lingkungan dalam Hadis - Muhammad Akmaluddin (JURNAL PENELITIAN, 2017)
A lack of understanding of religious texts, anthropocentric views, and the absence of integral human consciousness within the universe are among the causes of environmental damage. Understanding the prophetic environmental message in the hadith is one way to address these problems. The terms related to preserving the environment in the hadith are ḥafiẓa and ra‘ā, while those associated with destruction are fasada and halaka. By using a thematic approach to these terms in various hadith texts, several basic ideas about the prophetic environmental message delivered by Rasulullah (PBUH) can be identified. In preserving the environment, the prophetic messages include maintenance goals, inclusive ownership, positive contributions, use based on function, sustainable programs, limited use, and joint supervision in utilizing the environment. In contrast, environmental damage includes exploitative goals, exclusive ownership, negative contributions, incorrect use, unsustainable programs, unlimited use, and self-supervision. The religious texts on the environment in the hadith are not merely preserved texts. These texts should continually be brought to life in order to generate new interpretations in response to existing environmental phenomena.